Impression as History: José Daniel Carmona on the Maleku - Frajman, Eduardo (2021)
This essay explores de conditions of the Maleku indigenous people in Costa Rica at the end of the nineteenth century. Its focus is impressionistic, based on the chronicle of the last visit to the Maleku conducted by Bishop Bernardo Augusto Thiel, written by the priest José Daniel Carmona. The essay links Carmona’s remembrances with the conception of America developed by the historiographer Edmundo O’Gorman.